KARAKTERISTIK EMISI BLACK CARBON (BC) DARI PEMBAKARAN TERBUKA JERAMI PADI DAN DAMPAK TERHADAP KUALITAS UDARA AMBIEN - Hafidawati Hafidawati (EcoNews, 2018)
Crop residue open burning contribute the emission of Short lived Climate Forces (SLCF) pollutants thereby threat to global climate change. One of the them is Black carbon (BC). BC is estimated to be the second most potential greenhouse warming agent after Carbon Dioxide (CO2). In Cianjur district, West Java, open burning in the paddy field is common way to eliminate rice residues after harvesting. The main objective of this study was to assess the concentration of BC in ambient air from open burning of rice straw in Cugenang District, as well as assess the effect of the combustion efficiency of the emission BC. Experiment were conducted in District Cugenang at 8 studies sites for irrigated paddy field were carried out for eight varieties paddy (Mekongga, Cintanur, Ciherang, Hibrida, Inpari, Inul, Sarangue, Pandan wangi). The minivol sampler (5 Lpm) were used for PM2.5 sampling and smoke stain reflektometer EEL were used for analysis Black Carbon. BC concentration (µg/m3) in the eight fields burning experiments reported at 25oC, 1 atmosphere. The assess results, show that the net burn smoke of Black Carbon in µg/m3 averaged 85.91±2.26. The highest emissions came from the burning of hybrid varieties with a combustion efficiency of 93.1%. Black Carbon emissions are influenced by the efficiency of combustion, where combustion with flamming phase (> 90%) give higher emissions.